Population Genetics Reveals That the Western Tianshan Mountains Populations of Agrilus mali (Coleoptera: Buprestidae) May Have Not been Recently Introduced - Sun, Huiquan; Jia, Feiran; Zhao, Wenxia; Zhou, Zhongfu; Li, Chengjin; Wang, Jianjun; Yao, Yanxia (Frontiers in Genetics, 2022)
Agrilus mali Matsumura is a wood-boring beetle that aggressively attacks species of the genus Malus, and recently has caused serious damage to the wild apple tree M. sieversii (Lebed.) in the western Tianshan Mountains in Xinjiang. It was first detected in the western Tianshan Mountains in the early 1990s and spread rapidly, and was thus considered a regional invasive pest. To explore the possible outbreak mechanism of local population and characterize the genetic differentiation of A. mali across its range in China, we used three mitochondrial genes (COI, COII, and CytB) to investigate the genetic diversity and genetic structure of 17 A. mali populations containing 205 individuals collected from five provinces in China, among them 9 populations were from the western Tianshan Mountains. Ultimately, of the 136 pairwise FST comparisons, 99 showed high genetic differentiation among overall populations, and Tianshan populations exhibited significant differentiation with most of non-Tianshan populations. Also, A. mali populations represented relatively abundant haplotypes (54 haplotypes), especially nine populations from Tianshan Mountains showed prominence with 32 haplotypes, and 26 were unique, displayed relatively high genetic diversity. In addition, the Mantel test revealed population genetic differentiation in either overall populations or Tianshan Mountains populations probably be caused by geographical isolation. Phylogenic relationship showed that all populations clustered into three clades and Tianshan Mountains populations with CY occupied one of three clades. Those results would suggest that A. mali in the Western Tianshan region has possible experienced a long history, and may not be introduced recently. And the highly frequent gene flows within Tianshan populations possibly caused by human activities, which may enhance the adaptability of A. mali along the western Tianshan Mountains, leading to periodic outbreaks. The findings not only enhance our understanding of the jewel beetle population genetics, but also provide valuable information for pest management.